Fish contributions toward nutritional security in Kenya - Johnstone O. Omukoto; Nicholas A. J. Graham; Christina C. Hicks (Food Security, 2024)
Human nutrient deficiencies remain prevalent globally and are particularly common in low- and middle-income countries, such as Kenya. Fish holds potential to help address these deficiencies but remains barely incorporated in nutrition policies and strategies, partly due to a lack of supporting evidence. We address this gap by analyzing sixteen years of fisheries production and trade data from marine, freshwater, and aquaculture systems to evaluate fish nutrient supply, assess changes in supply, and determine the contributions the current supply could make to meet the nutritional needs of children under five years in Kenya. Despite an 11% increase, through time, in the total supply of fish, there was a 24% decline in per capita fish consumption due to fishery changes and increased fish demand. Furthermore, a 21% decline in supply of fish from inland freshwater systems resulted in a 25–40% decline in nutrient supply. Based on the current supply of fish, Kenya’s per capita consumption of 2.5 kg/yr is below WHO recommendations of 10.4 kg/yr. However, this supply has the potential to support nearly 13 million Kenyans at this WHO recommendation. If supply was targeted towards vulnerable groups, such as children under five years, it could supply all children in Kenya with one-third of their calcium, selenium, and protein and over 70% of children in Kenya with one-third of their iron, zinc, and omega-3 polyunsaturated fatty acids requirements. Therefore, fish can play an important role in supporting nutritional security in Kenya if strategic interventions involving all relevant sectors are considered, to reduce identified nutrient deficiencies.